Risk Management Analysis Using COBIT 4.1 at Vehicle Testing Management Information System - Resad Setyadi; Septian Anggoro (Maranatha University Press, 2021)
The role of information technology in an organization is growing so fast. Vehicle Testing of Management Information System (VTMIS) is a system that uses information technology to serve users in motor vehicle administration in the Banyumas transportation service area. VTMIS at the Banyumas Transportation Department is an integrated information system for the motor vehicle testing process starting from the registration process, levy payment, and vehicle testing. The purpose of this study is to analyze the risk management at VTMIS in Banyumas Transportation Department using Control Objective for Information and Related Technology (COBIT 4.1) domain Plan and Organize (PO) 9. COBIT 4.1 is a framework for analyzing and ensuring information technology aligns with business management by calculating maturity levels. The data analysis results from the PO9 domain show that VTMIS risk management has a maturity level of 3.46. The maturity level of VTMIS at the Banyumas Transportation Department is at level 3, namely defined, meaning that procedures are in a position of standardization, documentation, and individual communication. The recommendation for VTMIS at the Banyumas Transportation Department needs to carry out risk management in a structured, massive and integrated manner